Developing Learning Tools with Case-based Learning and Project-Based Learning for Digital Classroom Management Course - Asmiyunda Asmiyunda; Firdiawan Ekaputra; Affan Affan (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
The semester lesson plan is a learning tool used in higher education. The semester lesson plan was designed by applying case-based learning (CBL) and project-based learning (PjBL) models, which aim to achieve the target of course graduates. The digital classroom management course is new in the MBKM curriculum implemented in study programs. Therefore, it requires learning tools to support the implementation of lecture activities. This study aims to develop a semester lesson plan by applying valid and effective case-based learning (CBL) and project-based learning (PjBL) models in the learning activities. This research is development research with the ADDIE model. The subjects in the study were five lecturers and 30 students. The research produced a valid and effective semester lesson plan for digital classroom management courses.